In control, out of control or losing control? Making sense of men's reported experiences of coercive control through the lens of hegemonic masculinity. Issue 4 (December 2022) - Walklate, Sandra; Fitz-Gibbon, Kate; Reeves, Ellen; Meyer, Silke; McGowan, Jasmine
"I have never had a case that involved a female perpetrator of coercive control, and no such cases are documented in the literature" (Stark, 2007, p. 377). Stark's observation has become somewhat of a "truism" in the wider debate surrounding coercive control. Yet simultaneously coercive control is asserted as a gendered process, understandings of which appear to have elided and conflated victimhood and perpetration with femininity and masculinity. The purpose of this paper, based on empirical data, is to unpick some of these elisions and conflations and offer a more nuanced understanding of these debates using the lens of hegemonic masculinity. This paper is based on data derived from a national online survey conducted in Australia in 2021. The aim of this paper is to explore, and better understand male reported experiences of coercive control victimisation. The survey was completed by 1261 people, 206 (17%) of whom identified as men. These 206 responses are the focus of this paper. Representing one of the most comprehensive studies of men's self-reported experiences of coercive control, this survey data provides some insight into how male victim-survivors define and understand what they considered to be their experiences of coercive control. The findings provide an opportunity to offer a more nuanced appreciation of men's experiences of being in control, out of control or losing control.